2019
DOI: 10.3390/su11041166
|View full text |Cite
|
Sign up to set email alerts
|

Can “Liking” Behavior Lead to Usage Intention on Facebook? Uses and Gratification Theory Perspective

Abstract: The “like” feature on Facebook has emerged as a commonly used paralinguistic tool for communicating, and its importance as an indication of positive feelings toward the posts of others is likely to increase. Comprehensive research is needed into why and how users are motivated toward ‘liking’ behavior, and whether this behavior generates an intention to continue using Facebook over time. This study combines the theory of uses and gratification and a subjective norm perspective to create an integrated model tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 26 publications
2
48
1
4
Order By: Relevance
“…The results showed that the differential characteristics of UGEs in tourism were user empowerment, full organization, brand dissemination, attraction capacity, and online community loyalty. The research conducted by [12] found that the most important motivations for users to use a social network are enjoyment, information search and interaction, all elements treated in the present investigation. In line with this, [13] stated that quality of information was a key element in intention of continuous use for food distribution applications.…”
Section: Introductionmentioning
confidence: 74%
“…The results showed that the differential characteristics of UGEs in tourism were user empowerment, full organization, brand dissemination, attraction capacity, and online community loyalty. The research conducted by [12] found that the most important motivations for users to use a social network are enjoyment, information search and interaction, all elements treated in the present investigation. In line with this, [13] stated that quality of information was a key element in intention of continuous use for food distribution applications.…”
Section: Introductionmentioning
confidence: 74%
“…Previous studies have empirically validated the hypothesis that behavioral intentions of "Liking" are predicted by three aspects of gratification, hedonic, social, and utilitarian (Gan and Chunmei, 2017;Ozanne et al, 2017;Hossain et al, 2019). Hedonic gratification refers to enjoyment (Lee et al, 2016;Gan and Chunmei, 2017;Hossain et al, 2019;Shao and Kwon, 2019), entertainment (Kim, 2014;Ozanne et al, 2017), and passing time (Lee et al, 2016). Social gratification refers to social support (Hayes et al, 2016;Gan and Chunmei, 2017), interpersonal relationships (Lee et al, 2016), social interactions (Hossain et al, 2019), bonding (Ozanne et al, 2017), and socialization (Kim, 2014).…”
Section: Introductionmentioning
confidence: 95%
“…It has been demonstrated that hedonic gratification, social gratification, and utilitarian gratification can motivate "Like" intentions (Chin et al, 2015;Sun et al, 2016;Dhir et al, 2019;Hossain et al, 2019;Shao and Kwon, 2019;Wang et al, 2019). According to TPB, individual behavior is influenced by behavioral intention (Ajzen, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based previous literature on the continuous usage of SNS, our study suggests the factors affecting the sustainable use of mobile social apps which are showing much more business importance than desktop applications as business processes using smart devices become crucial in building business value. Thus, sustainability issues in continuous usage of social media [26][27][28][29][30] can be utilized in showing factors influencing the continuous usage of social apps.…”
Section: Individual Motivations and Social Capital For Adopting Mobilmentioning
confidence: 99%